A Sustainable Tourism Development Strategy in Manggarai Regency - Muljono, Virginia Felizia; Satrya, Dewa Gde (E-Journal of Tourism; Volume 9 Number 2 (September 2022)DO - 10.24922/eot.v9i2.87706, 2022)
The tourism development in Manggarai Regency, East Nusa Tenggara Province, on the one hand can improve the local economy, but on the other hand it needs to be carried out using the principles of sustainable tourism development. The purpose of this study is to describe the strategy of sustainable tourism development in Manggarai district after the Covid-19 pandemic. The research method is qualitative. The conclusion of this study is that Manggarai district has great potential for tourism development in aspects of culture, nature, and religion. The strategy for the development of sustainable tourism is first from the community perspective, using an emotional cultural approach to create a strong sense of belonging. In terms of infrastructure, it needs to be improved to increase the satisfaction of the community and tourists. Keywords: Development Strategy; Sustainable Tourism; Community Based Tourism.